Using 3GPP- A Secure IDS for MANETs - Garg, Monika; Kaur, Karanvir; Kaur, Simerpreet (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Mobile Ad hoc NETwork (MANET) is one of the important and unique applications. MANET does not require a fixednetwork infrastructure, every single node works as both a transmitter and a receiver. Nodes communicate directly witheach other when they are both within the same communication range else they can propagate message to neighbor nodesto pass the message. A new intrusion detection system named Enhanced Adaptive Acknowledgement (EAACK) speciallydesigned for MANETs. By the adoption of MRA scheme, EAACK is capable of detecting malicious nodes despite theexistence of false misbehavior report. The results will demonstrate positive performances against Watchdog, TWOACKand AACK in the cases of receiver collision, limited transmission power and false misbehavior report. EAACKdemonstrates higher malicious behavior detection rates in certain circumstances while does not greatly affect the networkperformances. EAACK is designed based on the Digital signature Algorithm (DSA) and RSA. Those techniques havedrawback due to network overhead. We need techniques for security like encryptions, hybrid encryption or sign encryptionto protect our message.